A Research Protocol of Hands-On Healthy Meal Preparation Intervention (Kidchen Study) to Improve Children’s Nutritional Outcomes - Kaur, Satvinder; Ming, Ng Choon; Chin, Koo Hui; Kuan, Roseline Yap Wai; Seng, Yim Hip; Mukhtar, Firdaus (Jurnal Gizi dan Pangan, 2020)
The objective of this paper is to describe the protocol of a 12-week hands-on healthy meal preparation intervention among children, up to a 3-month follow-up. The aim of KidChen Study (kids in kitchen) is to improve children’s nutritional outcomes. In this randomized-controlled trial, simple random sampling will be used to select schools in Kuala Lumpur, Malaysia. Subsequently, the selected schools (n=2) will be assigned randomly to either the intervention or control group. The current study will include healthy Malaysian children aged 10–11 years old with no serious disease or food allergy. The intervention is based on Social Cognitive Theory that addresses personal and environmental factors for changing children’s behaviour. Children from the intervention group will receive a 60-minute home food environment module with their parents consisting of nutrition talk, healthy food tasting, parent-child quiz; and five 60 minute interactive hands-on healthy meal preparation modules focusing on core food groups coupled withstorytelling sessions to incorporate nutrition education. Outcome measures are children’s psychosocial factors towards healthy meal preparation (knowledge, attitude, practice, self-efficacy), dietary behaviour, food consumption pattern, home food availability and anthropometric measures (BMI-for-age z-score, body fat percentage, waist circumference). Repeated measures ANOVA will be used to evaluate the intervention outcomes. KidChen Study is an experiential learning approach to instil a positive attitude towards nutrition and empower children with nutrition skills. We anticipate that the intervention will advocate healthy eating behaviour among children, impacting their nutritional outcomes over time.